Implementasi Model Problem Based Learning (PBL) yang Didukung Agen Pedagogi Terhadap Higher Order Thinking Skills (HOTS) dalam Pembelajaran Zoologi Invertebrata: Implementation of Problem Based Learning (PBL) Models Supported by Pedagogical Agents for Higher Order Thinking Skills (HOTS) in Learning Invertebrate Zoology - Kodri Madang; Mgs. Muhammad Tibrani; Lucia Maria Santoso (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2019)
This study aims to determine the effect of Problem Based Learning supported by pedagogical agents (PBL-PA) on Higher Order Thinking Skills (HOTS) of preservice teachers in Invertebrate Zoology Learning. This study uses a quantitative approach applied to 77 preservice teacher participating in the Invertebrate Zoology lecture in Biology Education, FKIP, Universitas Sriwijaya in Academic Year 2018/2019. The method used is Quasi Experimental with Nonequivalent Control Group Design. Determination of the sample through Simple Random Sampling so that PBL-AP (26 people), PBL (26 people), and traditional classes (25 people). HOTS ability is measured through pretest and posttest with 25 multiple choice questions that have been tested for validity and reliability. Hypothesis testing using Analysis of Covariance (ANCOVA) uses the SPSS 23 program. The results of the study indicate that the PBL-PA Methos has a significant effectiveness on the HOTS ability of preservice teacher. Furthermore, the PBL-PA is better than the PBL and traditional method in improving HOTS ability of preservice teacher. The PBL-PA Mothod can increase learning motivation and make students confident in formulating problems well in the early syntax of PBL. Keywords: Pedagogical Agents , Higher Order Thinking Skills, Problem Based Learning, Invertebrate Zoology Abstrak Penelitian ini bertujuan untuk mengetahui pengaruh model Problem Based Learning yang didukung agen pedagogi (PBL-AP) terhadap Higher Order Thinking Skills (HOTS) mahasiswa calon guru dalam Pembelajaran Zoologi Invertebrta. Penelitian ini menggunakan pendekatan kuantitatif yang diterapkan terhadap 77 mahasiswa calon guru peserta Perkuliahan Zoologi Invertebrata di Prodi Pendidikan Biologi, FKIP, Unsri pada Tahun Akademik 2018/2019. Metode yang digunakan adalah Quasi Experimental dengan desain Nonequivalent Control Group Design. Penentuan sampel dengan cara Simple Random Sampling sehingga diperoleh kelas PBL didukung agen pedagogi (26 orang), kelas PBL (26 orang), dan kelas tradisional (25 orang). Kemampuan HOTS diukur melalui pre-test dan post-test dengan instrumen 25 soal pilihan ganda yang telah teruji validitas dan reliabilitanya. Uji hipotesis menggunakan Analysis of Covariance (ANCOVA) menggunakan program SPSS 23. Hasil penelitian menunjukkan bahwa Model PBL-AP memiliki pengaruh yang signifikan terhadap kemampuan HOTS mahasiswa calon guru. Selanjutnya, model PBL-AP lebih baik dari pada model PBL dan tradisional dalam meningkatkan kemampuan HOTS mahasiswa calon guru. Model PBL-AP dapat meningkatkan motivasi belajar dan membuat peserta didik percaya diri dalam merumuskan permasalahan dengan baik pada tahap awal sintaks PBL. Kata kunci: Agen Pedagogi, Problem Based Learning, Higher Order Thinking Skills, Zoologi Invertebrata